Safety and immunogenicity of a candidate tuberculosis vaccine MVA85A delivered by aerosol in BCG-vaccinated healthy adults: A phase 1, double-blind, randomised controlled trial - Satti, I; Meyer, J; Harris, SA; Thomas, Z; Griffiths, K; Antrobus, R; Rowland, R; Ramon, R; Smith, M; Sheehan, S; Bettinson, H; McShane, H (Lancet, 2014)
Background: Intradermal MVA85A, a candidate vaccine against tuberculosis, induces high amounts of Ag85A-specific CD4 T cells in adults who have already received the BCG vaccine, but aerosol delivery of this vaccine might offer immunological and logistical advantages. We did a phase 1 double-blind trial to compare the safety and immunogenicity of aerosol-administered and intradermally administered MVA85A. Methods: In this phase 1, double-blind, proof-of-concept trial, 24 eligible BCG-vaccinated healthy UK adults were randomly allocated (1:1) by sequentially numbered, sealed, opaque envelopes into two groups: aerosol MVA85A and intradermal saline placebo or intradermal MVA85A and aerosol saline placebo. Participants, the bronchoscopist, and immunologists were masked to treatment assignment. The primary outcome was safety, assessed by the frequency and severity of vaccine-related local and systemic adverse events. The secondary outcome was immunogenicity assessed with laboratory markers of cell-mediated immunity in blood and bronchoalveolar lavage samples. Safety and immunogenicity were assessed for 24 weeks after vaccination. Immunogenicity to both insert Ag85A and vector modified vaccinia virus Ankara (MVA) was assessed by ex-vivo interferon-γ ELISpot and serum ELISAs. Since all participants were randomised and vaccinated according to protocol, our analyses were per protocol. This trial is registered with ClinicalTrials.gov, number NCT01497769. Findings: Both administration routes were well tolerated and immunogenic. Respiratory adverse events were rare and mild. Intradermal MVA85A was associated with expected mild local injection-site reactions. Systemic adverse events did not differ significantly between the two groups. Three participants in each group had no vaccine-related systemic adverse events; fatigue (11/24 [46%]) and headache (10/24 [42%]) were the most frequently reported symptoms. Ag85A-specific systemic responses were similar across groups. Ag85A-specific CD4 T cells were detected in bronchoalveolar lavage cells from both groups and responses were higher in the aerosol group than in the intradermal group. MVA-specific cellular responses were detected in both groups, whereas serum antibodies to MVA were only detectable after intradermal administration of the vaccine. Interpretation: Further clinical trials assessing the aerosol route of vaccine delivery are merited for tuberculosis and other respiratory pathogens. Funding: The Wellcome Trust and Oxford Radcliffe Hospitals Biomedical Research Centre.